PERANCANGAN APLIKASI INFORMASI PENDAKIAN GUNUNG DI INDONESIA BERBASIS ANDROID DENGAN MENGGUNAKAN METODE PROTOTYPE - Fauzi, Aditya Ahmad; Adisuputra, Adisuputra (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
Nowadays, more and more teenagers and adults are interested in mountain climbing. Climbers are keen to find information about the routes and mountains they will be climbing. However, many mountaineers complain that the information they get about climbing routes is not accurate or complete. The information currently available is only general information and does not have accurate data such as coordinate points, mountain profiles, transportation facilities, and other facilities that help climbing. To solve this problem, Object Oriented Design (OOD) and Prototype system development methods were used to create an Android-based Indonesian mountaineering information application. The application was developed using Android Studio and designed to provide comprehensive information for mountaineers, including paths to the mountain, photo galleries, current news about the mountain to be climbed, climbing posts, and geographical locations. The study resulted in contributions in various aspects that can improve the safety and comfort of mountaineers in Indonesia. With more accurate and complete information and the utilization of modern technology, this application supports mountaineering activities significantly. Climbers not only get better guidance but also feel safer and more comfortable in pursuing their hobby.